2014
DOI: 10.1093/icvts/ivu295
|View full text |Cite
|
Sign up to set email alerts
|

Does the extent of resection affect survival in patients with synchronous multiple primary lung cancers undergoing curative surgery?: Table 1:

Abstract: A best evidence topic was written according to a structured protocol. The question addressed was whether the extent of pulmonary resection affects survival in patients with synchronous multiple primary lung cancers undergoing curative surgery. A total of 724 papers were identified using the reported searches, of which 14 represented the best evidence to answer the clinical question. The authors, date, journal, country, study type, population, outcomes and key results are tabulated. All studies were retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…This was also con rmed by the ndings of this study. Similarly, other previous studies [1,14,17,18] did not demonstrate a signi cant difference in prognosis with respect to lobectomy versus sublobectomy for the second tumor. The choice of surgery for the second primary tumor is challenging for thoracic surgeons, especially for patients with history of lobectomy or pneumonectomy.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This was also con rmed by the ndings of this study. Similarly, other previous studies [1,14,17,18] did not demonstrate a signi cant difference in prognosis with respect to lobectomy versus sublobectomy for the second tumor. The choice of surgery for the second primary tumor is challenging for thoracic surgeons, especially for patients with history of lobectomy or pneumonectomy.…”
Section: Discussionsupporting
confidence: 76%
“…In clinical practice, the relative location of two primary tumors had an extremely important in uence on the nal selection of surgical procedure. Generally speaking, when two tumor lesions were in the ipsilateral different lobes, lobectomy for the second lesion tended to lead to pneumonectomy, which was a risk factor affecting the prognosis of patients [4,14,18]. This study found that when the two lesions were in the ipsilateral different lobes, wedge resection demonstrated equivalent OS to lobectomy.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…An optimal surgical method for SBMPLC is lacking (16)(17)(18). Lobectomy remains first-line treatment for earlystage NSCLC but a single-stage bilateral lobectomy is not recommended due to the severe trauma imparted.…”
Section: Discussionmentioning
confidence: 99%
“…Sublobar resections should also be considered in patients with metachronous or synchronous primary lung cancer, especially in patients with prior resections and with poor predicted remnant pulmonary reserve (56,(61)(62)(63)(64)(65)(66)(67)(68)(69). The majority of studies examining the role of sublobar resections in multiple primary lung cancer have not found a difference in survival when compared to lobectomy (62)(63)(64)(65)(66)(67)(68)(69). Some patients with evidence of less aggressive lung cancer, namely minimally invasive adenocarcinoma (MIA) or adenocarcinoma in situ (AIS), may also be candidates for sublobar resections.…”
Section: Extent Of Surgery: Effectiveness Of Lobar and Sublobar Resecmentioning
confidence: 99%